A New Path for Drug Delivery by Multiple Unit Pellet System (MUPS) - Bafna, Harshada Rajendra (Indian Journal of Pharmacy & Drug Studies, 2025)
Innovative delivery system that are helpful in enhancing therapeutic objectives and reducing adverse effects are the focus of pharmaceutical research. The advantages of tablets and pellet-filled capsules are combined into a single dose form by MUPS, one of the more complex and inventive technologies. Continuous drug distribution into the bloodstream is made possible by the breakdown of these pills in the stomach and intestine. The current article examines the potential benefits, desirable pellet characteristics, different pelletization methods, MUPS-influencing factors, drug release mechanisms, and pharmaceutical applications, as well as the challenges associated with compaction and the crucial elements that must be considered for MUPS production to be successful.